(untitled) (The Review of Diabetic Studies, 2021)
BACKGROUND: Peripheral artery disease (PAD) and diabetes mellitus are factors known to influence gait characteristics. However, there is a lack of knowledge on the extent to which type 2 diabetes mellitus (T2D) and PAD as comorbidities cause limb and gait complications. AIM: The purpose of this study was to investigate the impact of PAD as a complication of T2D on ankle joint dorsiflexion and knee joint flexion angles using an optoelectronic motion analysis system and to find out whether these alterations are complications secondary to neuropathy or reduced blood perfusion. METHODS: Ninety participants were recruited in this quantitative study which applied a prospective, comparative, non-experimental approach. Participants with T2D and PAD (n = 60), categorized according to the severity of PAD (mild and severe group), were compared with a control group consisting of patients with T2D alone. An optoelectronic motion capture system was used to record mean maximum flexion angles of the knee joint and maximum mean dorsiflexion angles of the ankle joint during gait. RESULTS: 180 limbs were analyzed. Both mild and severe PAD participants exhibited a significant increase in mean maximum ankle joint dorsiflexion angles (p = 0.001) and a significant decrease in mean maximum flexion of the knee joint compared with the control subjects (p = 0.001). CONCLUSIONS: This study shows that T2D and PAD alter ankle joint and knee joint kinematics. This research provides biomechanical understanding of limb and gait alterations in this specific patient population which may contribute to an improved understanding of gait alterations and clinical management. The findings suggest that the reduction in ankle joint dorsiflexion commonly attributed to glycosylation in diabetes may be secondary to neuropathy and not to reduced blood perfusion.